An update on niche composition, signaling and functional regulation of the adipose-derived stem cells. (August 2014) - Kim, Won-Serk; Han, Juhee; Hwang, Sung-Joo; Sung, Jong-Hyuk
Abstract : Introduction: The self-renewal and differentiation of stem cells are controlled by both intrinsic factors and the surrounding microenvironment, which is known as the stem cell niche. Although the niches of adipose-derived stem cells (ASCs) are composed of diverse factors within the adipose tissue, the mechanisms by which niches are maintained, regulated and harmonized to support the ASCs are just beginning to be discovered. Areas covered: This review introduces the recent advances in the anatomic nature of the dynamic in vivo niches of ASCs. Additionally, new findings concerning the signaling pathways involved in the self-renewal, proliferation, differentiation and paracrine mechanisms will be described. Finally, we suggest optimized methods for expanding ASCs in vitro by mimicking the niche factors to enhance the regenerative potential of ASCs. Expert opinion: Fibroblast growth factor 2 is a self-renewal factor that can expand the lifespan of ASCs in long-term culture and platelet-derived growth factor-B/D has most potent mitogenic effects on short-term ASC expansion. Reactive oxygen species donors and stimulators of the phosphoinositide 3-kinase/protein kinase B and MAPK pathways can be used to increase the production yield of ASCs. Additionally, hypoxia can increase the proliferation of ASCs and priming under hypoxic conditions enhances the regenerative potential of ASCs.